2018
DOI: 10.4031/mtsj.52.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Satellite-Derived SST Products in Identifying the Rapid Temperature Drop on the West Florida Shelf Associated With Hurricane Irma

Abstract: Satellite-derived daily sea surface temperature (SST) products are compared with moored SST observations on the West Florida Shelf during the time period of Hurricane Irma. Most of the SST products compare reasonably well with the moored data at the location of 25-m depth, where SST dropped by about 1°C after the hurricane passage. However, most of the SST products did not show the rapid SST drop at the location of 50-m depth where the surface water was cooled by about 4°C within 1 day in response to the hurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The wind data strongly indicate that cyclone Dorian was, in fact, the cause of the marked decrease of intertidal SST on 8 September. At lower latitudes, tropical hurricanes decrease SST in offshore environments due to shear-induced vertical mixing of waters, as subsurface layers of the ocean are typically cooler than surface layers, especially in summer (Korobkin et al, 2009;Lai et al, 2015;Glenn et al, 2016;Seroka et al, 2016;Liu et al, 2018). The timing of the sharp SST drop observed after the passage of Dorian agrees with observations made for tropical hurricanes (Rao et al, 2004).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The wind data strongly indicate that cyclone Dorian was, in fact, the cause of the marked decrease of intertidal SST on 8 September. At lower latitudes, tropical hurricanes decrease SST in offshore environments due to shear-induced vertical mixing of waters, as subsurface layers of the ocean are typically cooler than surface layers, especially in summer (Korobkin et al, 2009;Lai et al, 2015;Glenn et al, 2016;Seroka et al, 2016;Liu et al, 2018). The timing of the sharp SST drop observed after the passage of Dorian agrees with observations made for tropical hurricanes (Rao et al, 2004).…”
Section: Discussionsupporting
confidence: 68%
“…Cyclones are extreme cases of wind forcing. Given their capacity for vertical mixing of upper ocean layers (Seroka et al, 2016;Liu et al, 2018), cyclones might also generate significant thermal fluctuations in intertidal habitats at hourly scales. However, this seems not to have been examined quantitatively, probably because of the low frequency of occurrence of coastal cyclones in comparison with tides and regular upwelling events.…”
Section: Introductionmentioning
confidence: 99%
“…The warm-biased TC wakes in ATM could indicate that the cooling feature in OSTIA occurs after the end of the simulations. Also, 635 comparisons of OSTIA observations to moored buoys have shown that cyclone cold wakes can be poorly captured in OSTIA (Liu et al, 2018) due to the difficulty in obtaining accurate satellite SST measurements through thick clouds such as those associated with cyclones (Sunder et al, 2020). TC simulations are sensitive to initial SST conditions, as well as coupling (Feng et al, 2019).…”
mentioning
confidence: 99%
“…If in situ SST data were available, the observed SST could be different. This is because most satellite-derived SST products might underestimate the rapid SST drop associated with hurricane/typhoon passage [38]. The SST dropped 4 degrees Celsius within one day after the passage of Hurricane Irma [38].…”
mentioning
confidence: 99%